Sedation Quality of Low – Dose Ketamine Combined with Dexmedetomidine versus Propofol in Phacoemulsification under Local Anesthesia: A Triple-Blinded Randomized Clinical Trial: Doi: 10.36351/pjo.v39i3.1629 - Nazemroaya, Behzad; Koosha, Nima; Moradi Farsani , Darioush; Khosropour, Ali (Pakistan Journal of Ophthalmology, 2023)
Purpose: To compare the hemodynamic effects of low-dose ketamine combined with dexmedetomidine versus propofol in phacoemulsification under local anesthesia. Place and Duration of Study: School of Medicine, Isfahan University of Medical Sciences during 2020-2021. Methods: Sixty patients admitted for cataract surgery were included. Those with history of systemic diseases, insufficient pupil dilation, sensitivity to drugs and uncooperative patients were excluded. Participants were randomly allocated to two groups; group which was administered ketamine with dexmedetomidine (Ketodex) and group which was given ketamine with propofol (Ketofel). Effect on blood pressure, pulse and sedation was recorded. Results: Mean age was 65 ± 9.9 years. Sixty-five were females. Ketodex increased the risk of hemodynamic disorders compared to Ketofel (P = 0.04). The risk of nausea and vomiting was higher in the Ketodex group although not significant. The effect of drug course on heart rate, blood pressure and sedation was significant in both groups (P < 0.05). Neither at baseline, nor in the 1st and 5th minutes of surgery, was the mean arterial pressure (MAP) was significantly different between the two groups. From 10th minute of surgery until the end of surgery and from the beginning of recovery until the 30th minute of recovery, the MAP and pulse rate were higher in Ketofol group. Sedation effect during surgery was higher in the Ketodex group compared to the Ketofol group, and the difference was statistically significant at minutes 10, 20 and 30 of surgery. Conclusion: There is higher effect of sedation and fewer side effects of ketamine-dexmedetomidine combination compared to the ketamine-propofol combination.